2019
DOI: 10.26900/jsp.3.023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Regularly Exercise in Overcoming Infertility Barriers

Abstract: Infertility is seen worldwide in developing countries and affects 30% of couples. Infertility causes depression, anxiety, social isolation, sexual dysfunction and decreased quality of life. In the treatment of infertility; besides medical treatment, significant advances have been obtained from the eastern medical strategies. Regular exercise programs, physical fitness are given to individuals. In addition, it makes them feel good about themselves physically and spiritually. It has been shown that exercise has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…76 In addition, several evidence indicated that lifestyles such as physical activity and unhealthy diets could impact fertility and sperm function. 92,93 High-fat diet and diet enriched advanced glycation end products dysregulated the function, parameters, and intracellular reactive oxygen species of sperm. 92 Furthermore, the high-fat diet enriched AGEs enhanced the inflammation and apoptotic signaling pathway in the intestinal of the mice.…”
Section: Non-coding Rnas and Oxidative Stress In The Management Of Ty...mentioning
confidence: 99%
“…76 In addition, several evidence indicated that lifestyles such as physical activity and unhealthy diets could impact fertility and sperm function. 92,93 High-fat diet and diet enriched advanced glycation end products dysregulated the function, parameters, and intracellular reactive oxygen species of sperm. 92 Furthermore, the high-fat diet enriched AGEs enhanced the inflammation and apoptotic signaling pathway in the intestinal of the mice.…”
Section: Non-coding Rnas and Oxidative Stress In The Management Of Ty...mentioning
confidence: 99%